Strategies and goals in Emotion Regulation models: a systematic review - Martínez-Priego, Consuelo; García-Noblejas, Belén Poveda; Roca, Pablo (Frontiers in Psychology, 2024)
Introduction: Studies examining the role of Emotion Regulation (ER) do not consistently explain the underlying model or theory they are employing, resulting in a conflation of different strategies and goals within the ER scientific literature. This study aims to conduct a systematic review and conceptual analysis of the primary strategies and goals advocated in the ER models, theories, and frameworks. Furthermore, we explored the distinctions between the prevailing contemporary ER models and classical conceptions of emotional dynamics, such as those proposed by Aristotle, Descartes, and Darwin.: An electronic search was conducted in the Web of Science, Medline, and Scopus databases in November 2023. The key search terms used were grouped into two different topics: Emotion Regulation and Models/Theories/Frameworks. Articles were included if they reported one or more ER model in healthy individuals or emotionally disordered individuals and if they were published in a peer-reviewed journal in English in the last 5 years (from 2019 to 2023). A total of 2 reviewers independently assessed the titles, abstracts, and full texts. Models identified were summarized and classified based on the different ER strategies and goals. Results: Of the 1012 titles for initial consideration, 139 articles met the full eligibility criteria and were included for data extraction and synthesis. The review identified 10 ER models, and the most commonly used were the Process Model of Emotion Regulation (Gross, 1998) and the Difficulties in Emotion Regulation (Gratz and Roemer , 2004). There was a great deal of homogeneity among the proposed ER strategies and goals: the cognitive dimension is the core of ER strategy, and the ER goals are primarily hedonic or instrumental in nature.Discussion: Both Descartes and Darwin views were present in the ER models; however, some of the most significant contributions in Aristotelian proposal seem to be forgotten, such as the integration of the physical, operational, and growth dimensions (eudaimonic goals).Systematic review registration: This systematic review was conducted in accordance with the PRISMA guidelines and was preregistered at Prospero platform (masked for review).